Spectrophotometric Determination of Phycobiliprotein Content in Cyanobacterium Synechocystis - Zavřel, Tomáš; Chmelík, Dominik; Sinetova, Maria A; Červený, Jan (Journal of visualized experiments, 2018)
This is a simple protocol for the quantitative determination of phycobiliprotein content in the model cyanobacterium Synechocystis. Phycobiliproteins are the most important components of phycobilisomes, the major light-harvesting antennae in cyanobacteria and several algae taxa. The phycobilisomes of Synechocystis contain two phycobiliproteins: phycocyanin and allophycocyanin. This protocol describes a simple, efficient, and reliable method for the quantitative determination of both phycocyanin and allophycocyanin in this model cyanobacterium. We compared several methods of phycobiliprotein extraction and spectrophotometric quantification. The extraction procedure as described in this protocol was also successfully applied to other cyanobacteria strains such as Cyanothece sp., Synechococcuselongatus, Spirulina sp., Arthrospira sp., and Nostoc sp., as well as to red algae Porphyridium cruentum. However, the extinction coefficients of specific phycobiliproteins from various taxa can differ and it is, therefore, recommended to validate the spectrophotometric quantification method for every single strain individually. The protocol requires little time and can be performed in any standard life science laboratory since it requires only standard equipment.
Keywords: rostlinné proteiny; Spectrophotometry; Cyanobacteria; Plant Proteins; fykobiliproteiny; sinice; Synechocystis; Phycobiliproteins; spektrofotometrie